Distributed modelling of cell population - Jędruch, Wojciech; Waniewski, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
A distributed approach to modelling of population processes is discussed, and a few examples of simulations generated by an abstract universe - a universal modelling environment - are presented.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka